2008
DOI: 10.1088/0957-4484/19/46/465608
|View full text |Cite
|
Sign up to set email alerts
|

The development of stable aqueous suspensions of PEGylated SPIONs for biomedical applications

Abstract: We report here the development of stable aqueous suspensions of biocompatible superparamagnetic iron oxide nanoparticles (SPIONs). These so-called ferrofluids are useful in a large spectrum of modern biomedical applications, including novel diagnostic tools and targeted therapeutics. In order to provide prolonged circulation times for the nanoparticles in vivo, the initial iron oxide nanoparticles were coated with a biocompatible polymer poly(ethylene glycol) (PEG). To permit covalent bonding of PEG to the SPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 34 publications
16
101
1
Order By: Relevance
“…Because polyethylene glycol (PEG) coatings stabilize MNPs in physiological fl uids and impart an additional biocompatibility to the system for applications in neuronal cultures, [ 34 ] carbodiimide chemistry was used to graft 10 kDa PEG chains onto the poly(acrylic acid) (PAA)-passivated water-soluble MNPs. In order to ensure close proximity during AMF application, MNPs must be specifi cally targeted to Aβ aggregates.…”
Section: Targeting Mnps To Aβmentioning
confidence: 99%
See 1 more Smart Citation
“…Because polyethylene glycol (PEG) coatings stabilize MNPs in physiological fl uids and impart an additional biocompatibility to the system for applications in neuronal cultures, [ 34 ] carbodiimide chemistry was used to graft 10 kDa PEG chains onto the poly(acrylic acid) (PAA)-passivated water-soluble MNPs. In order to ensure close proximity during AMF application, MNPs must be specifi cally targeted to Aβ aggregates.…”
Section: Targeting Mnps To Aβmentioning
confidence: 99%
“…While the biocompatibility of iron oxide MNPs has been established in numerous in vitro and in vivo studies, [29][30][31][32]34 ] including our earlier work, [ 40 ] here we aimed to evaluate the potential neurotoxic effects of magnetothermal disaggregation of Aβ. Specifi cally, a number of reports indicate that soluble Aβ oligomers may yield greater neurotoxicity than larger aggregates.…”
Section: Effect Of Magnetothermal Disruption Of Aβ Aggregates On Neurmentioning
confidence: 99%
“…Indeed, PEG is a well-known material in providing protein adsorption resistance [42]. This strategy is mostly used for drug delivery, while no reports are present in the literature with respect to bioassays [43,44]. Afterwards, the G6 peptide was conjugated on PEG-MP obtaining a surface conjugation density of 12.5 Â 10 12 peptide cm 22 corresponding to an average distance between each peptide of approximately 30 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Several examples show how peptide can be conjugated to MP. However, none of them report about the use of antifouling surfaces such as PEG decorated with targeting peptide for diagnostic applications [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…PEG is an attractive polymer for reducing opsonization due to its uncharged and hydrophilic nature Chess, 2003, Harris et al, 2001). It has been shown that the presence of PEG chains on the nanocarrier surface increases both the colloidal stability in physiological conditions (Hervé et al, 2008) and the in vivo blood half-life . The stealthiness of a PEGylated nanocarrier can also be affected by parameters such as the polymer molecular weight, as well as its density and conformation on the nanocarrier surface , Peracchia et al, 1997.…”
Section: Introductionmentioning
confidence: 99%